An Acceptable time - L'Engle, Madeleine (Bantam Doubleday Dell Books for Young Readers, 1990)
Polly O'Keefe goes to spend a quiet visit with her grandparents. She meets several unusual people, who lead her on a trip back through time, where she discovers the importance of love in human relationships.